Molecular Docking and Clustering of Apple (Malus sylvestris Mill) and Date (Phoenix dactylifera L.) Metabolites as Anti-Inflammatory Agents - Amanda Oktaviani Setiawan; Dr. Harry Noviardi; Nina Imaniar (Sains Natural: Journal of Biology and Chemistry, 2026)
Inflammation is the body's defense response to infections, physical injuries, metabolic disorders, and autoimmune diseases. Foreign agents will attach to TLR (Toll Like Receptor) and initiate the activationNF-κB within nucleus. This signaling induce release of IL-1β, IL-6, TNF-α, and iNOS. The manalagi apple and sukari date fruit are known to have bioactive compounds like flavonoids and phenols that could help reduce inflammation. This study seeks to identify the potential compounds in Malus sylvestris Mill, and Phoenix dactylifera L. as anti-inflammatory agents that inhibit the cytokines IL-1β, IL-6, TNF-α, and iNOS. These compounds were tested with parameters such as binding affinity (∆G), inhibition constant (Ki), physicochemical properties, absorption, distribution, metabolism, excretion, and toxicity (ADMET), as well as molecular dynamics. Ellagic acid, one of the 76 compounds obtained, has the potential to be an effective anti-inflammatory agent. It inhibits IL-1β (-4.901 kkal/mol and 0.9918 uM), IL-6 (-6.424 kkal/mol and 0.9892 uM), iNOS (-8.597 kkal/mol and 0.9856 uM), and TNF-α (-9.347 kkal/mol and 0.9843 uM). Ellagic acid has a molecular weight of 302.194 g/mol, a LogP partition coefficient of 1.3128, 4 hydrogen donors, and 8 hydrogen acceptors. Ellagic acid also has good ADME properties with a toxicity class of 6, non-mutagenis, and non-hepatotoxic.